2020
DOI: 10.20885/jsb.vol24.iss2.art1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting green product purchase: Applying a Cognitive-Affective-Behavior hierarchy

Abstract: There are three major elements that considered being the expected certainty in green product purchasing is environmental attitude, product attitude, and also purchasing intention. Other variables such as collectivism, individualism, subjective and objective knowledge, environmental awareness, government's role, media exposure, social influence, and perceived monetary value are linked to these factors as well. This research aims to examine regarding Indonesian consumers' in creating green product purchase inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…Research on social influence has found that people that are classified into the same social group have a tendency to behave the same as their group (Jacob, Putri, Sihombing, 2020). This kind of behaviour lies in the concept called homophily, in which individuals will try to affiliate themselves with others by displaying the similar or even the same kind of behaviour.…”
Section: Social Influencesmentioning
confidence: 99%
“…Research on social influence has found that people that are classified into the same social group have a tendency to behave the same as their group (Jacob, Putri, Sihombing, 2020). This kind of behaviour lies in the concept called homophily, in which individuals will try to affiliate themselves with others by displaying the similar or even the same kind of behaviour.…”
Section: Social Influencesmentioning
confidence: 99%